SUFFERINGS OF THE PALESTINIANS IN UNDERGOING THE FASTING MONTH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 21 June 2016 – As it is in Malaysia, Ramadhan is ushered in by the Palestinians by intensifying their religious activities to gain the rewards which have been doubled as promised by Allah SWT throughout the said month.